Application of e-RKAM in Electronic-Based Madrasah Planning and Budgeting in the Ministry of Religion of South Sumatra Province - Putri, Sapta Dwi; Sakapurnama, Eka (Newinera Publisher, 2024)
Realizing quality education starts from good governance and management. The e-RKAM application is one of the breakthroughs that can help the Ministry of Religion to plan the needs of madrasas more efficiently. Through this application, madrasas can be assisted in terms of managing administration starting from the planning, budgeting, and reporting processes. With e-RKAM, good governance can be realized by integrating various things, namely in terms of supervision, control, and institutional accountability. The e-RKAM system is also a reflection of one of the digital transformations in madrasas. With the policy implementation approach from Edward III, policy recommendations can be taken by stakeholders, especially the Central Ministry of Religious Affairs, in terms of improving institutional governance that is transparent, effective and efficient and can have a direct impact on the quality of learning. So that in the future the BOS budget allocation is no longer based on the number of students, but on the performance of each madrasah and how well the activity program is designed. UTAUT's approach to see the application of technology, in this case the e-RKAM application, is related to its ease of use and usefulness for madrasas.